Preparation method of corrosion-resistant photovoltaic packaging material
By modifying the hydroxyl and siloxane segments on the surface of the composite particles and modifying the UV-resistant groups, polymerizing self-assembly fillers to form crosslinked double bonds, combining ethylene gas and vinyl acetate polymerization to prepare modified EVA, the problem of insufficient corrosion resistance and UV resistance of photovoltaic packaging materials is solved, and the performance and service life of the material are significantly improved.
Patent Information
- Application Number
- CN202411943048.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
AI Technical Summary
The corrosion resistance and UV resistance of existing photovoltaic packaging materials need to be further improved.
By modifying the hydroxyl and siloxane segments on the surface of composite particles with a two-component silicon titanium, and modifying the UV-resistant group on the cyclic silicon monomer, the self-assembly filler with surface crosslinked double bonds is obtained by mixing and capping the two, self-assemblying with ethylene gas, and then polymerizing with vinyl acetate solution to obtain modified EVA, and melt blended with auxiliary materials to extrude to obtain corrosion-resistant and ultraviolet-resistant photovoltaic packaging material.
It significantly improves the corrosion resistance and UV resistance of photovoltaic packaging materials, enhances the mechanical strength and cross-linking of the material, and extends the service life of the photovoltaic panel.
Smart Images

Figure BDA0005212988970000041 
Figure BDA0005212988970000051 
Figure BDA0005212988970000053
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photovoltaic packaging, and in particular to a method for preparing a corrosion-resistant photovoltaic packaging material. Background Art
[0002] The development history of photovoltaic encapsulation materials has always been centered around improving the durability and efficiency of photovoltaic modules. Initially, the photovoltaic industry generally used EVA as an encapsulation material because of its good light transmittance and adhesion, which can effectively protect solar cells. However, EVA has weak resistance to ultraviolet rays and is prone to yellowing and degradation over time, affecting the photoelectric conversion efficiency and service life of photovoltaic panels. With the advancement of technology, some new materials such as ion exchange resins and silica gel encapsulation materials have also begun to be used. These materials provide better heat resistance and weather resistance, which can further improve the stability and life of photovoltaic modules under extreme climatic conditions. The development of photovoltaic encapsulation materials is moving towards higher durability, better environmental adaptability and longer service life.
[0003] Prior art CN114854331B discloses a UV cut-off EVA photovoltaic adhesive film, a preparation method thereof and a photovoltaic module. The raw material formula of the UV cut-off EVA photovoltaic adhesive film is as follows by weight percentage: 87-98% EVA resin, 0.05-5% antioxidant, 0.25-2% cross-linking agent, 0.1-4% silane coupling agent, 0.1-4% UV absorber, 0.05-4% nano metal oxide and 0.1-8% anti-PID functional material. The UV absorber is p-dimethylaminocinnamoyloxypropyltrimethoxysilane. Through the coordinated coordination of various raw materials, the film has excellent UV cut-off and anti-PID effects and can maintain excellent visible light transmittance.
[0004] However, the above patent content is to achieve the purpose of improving the UV cutoff of the EVA photovoltaic film through the synergistic coordination of various raw materials. However, the polarity difference between the UV absorber and the nano metal oxide is large, which leads to weak interfacial bonding between the two, reducing the synergistic coordination ability between the two, resulting in the material's UV resistance to be further improved. In addition, due to the weak corrosion resistance of the EVA resin itself, the material's corrosion resistance also needs to be further improved.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a corrosion-resistant photovoltaic encapsulation material, so as to solve the technical problem in the prior art that the corrosion resistance and UV resistance of photovoltaic encapsulation materials need to be further improved.
[0007] The object of the present invention can be achieved by the following technical solution: A method for preparing a corrosion-resistant photovoltaic encapsulation material comprises the following steps:
[0008] S1. Place the self-assembly filler and azobisisobutyronitrile in a high-pressure reactor, increase the temperature of the high-pressure reactor to 120-150° C., increase the pressure to 12-16 MPa, introduce ethylene, and polymerize at constant temperature and pressure for 40-60 minutes to obtain a modified EVA precursor;
[0009] The reaction principle for preparing the anti-EVA precursor is: under the catalysis of free radical initiator and high temperature and high pressure, ethylene gas and carbon-carbon double bonds on the surface of self-assembled filler undergo polymerization reaction, and finally a modified EVA precursor is prepared.
[0010] S2, adding the modified EVA precursor, vinyl acetate and o-xylene into a reactor, raising the temperature of the reactor to 120-130°C, stirring for 10-15 minutes, adding azobisisobutyronitrile into the reactor, keeping the temperature for 1-2 hours, and post-treating to obtain the modified EVA;
[0011] The reaction principle for preparing modified EVA is: under high temperature and catalysis of a free radical initiator, the carbon-carbon double bonds on the modified EVA precursor and the double bonds on vinyl acetate undergo solution polymerization to obtain modified EVA.
[0012] S3, adding the modified EVA and auxiliary materials into a twin-screw extruder, and melt-extrude to obtain photovoltaic encapsulation materials.
[0013] Furthermore, in step S1, the amount ratio of self-assembly filler, azobisisobutyronitrile and ethylene is 10-20g:2-3g:80-90g; in step S2, the amount ratio of modified EVA precursor, vinyl acetate, o-xylene and azobisisobutyronitrile is 7-8g:2-3g:30-40mL:0.5-0.8g, and post-treatment includes: after the reaction is completed, the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and reduced pressure distillation is performed until no liquid is extracted to obtain modified EVA.
[0014] Furthermore, in step S3, the amount ratio of modified EVA and auxiliary materials is 85-90g:10-15g, the auxiliary materials include ultraviolet absorber, antioxidant, plasticizer and cross-linking agent, the amount ratio of ultraviolet absorber, antioxidant, plasticizer and cross-linking agent is 0.5-2g:0.5-1g:4-5g:5-7g, and the temperatures of 8 temperature zones of the twin-screw extruder from the feed end to the discharge end are 180°C, 185°C, 195°C, 195°C, 210°C, 215°C, 215°C, and 220°C, respectively, and the spindle speed of the twin-screw extruder is 60-80rpm, and the pressure is 100-150bar.
[0015] Furthermore, the ultraviolet absorber is one or more of 2-hydroxy-4-octyloxyphenol, 2-hydroxy-4-methoxybenzophenone and 2-(2'-hydroxy-5'-methylphenyl)benzotriazole; the antioxidant is one or more of 2,6-di-tert-butyl-p-cresol, 6-hydroxy-2,2,4-trimethyl-1,2-dihydroquinoline and triphenyl phosphate; the plasticizer is one or more of dioctyl phthalate, butyl benzyl phthalate and diisobutyl phthalate; the crosslinker is one or more of tert-butyl peroxide bis(2-ethylhexanoate), tris(dimethylaminomethyl)phenol and methyltrimethoxysilane.
[0016] Further, the modified cyclosilane, self-assembly substrate and ether are added to the reactor, stirred at room temperature for 12-16 minutes, and then 98.0wt% sulfuric acid solution is added dropwise to the reactor. The reaction is kept warm for 4-5 hours at room temperature, and the terminator is continued to be added to the reactor. After the reaction for 2-4 hours, solid sodium bicarbonate is added to the reactor until the pH of the reaction solution is 7-8, and the self-assembly filler is obtained by post-treatment.
[0017] The reaction equation for preparing the self-assembled filler is:
[0018]
[0019] The reaction principle for preparing self-assembling fillers is as follows: under the action of concentrated sulfuric acid as an initiator, the self-assembling substrate and the modified cyclosilane undergo a polymerization reaction, and the chain initiation process starts with the silane structure on the self-assembling substrate as the base point. As the reaction progresses, the terminator 1,3-divinyl-1,3-dimethyl-1,3-diphenyldisiloxane is continuously introduced into the reaction system to form an organic chain segment structure terminated with a vinyl group.
[0020] Furthermore, the amount ratio of modified cyclosilane, self-assembly substrate, ether, 98wt% sulfuric acid solution and terminator is 5-6g:8-10g:40-60mL:1-2mL:2-3g, the terminator is 1,3-divinyl-1,3-dimethyl-1,3-diphenyldisiloxane, and the post-treatment includes: filtering the reaction liquid to collect the filter cake, washing the filter cake with anhydrous ethanol and deionized water for 3-5 times, transferring the filter cake to a drying oven at a temperature of 60°C and vacuum drying it until the filter cake has a constant weight to obtain a self-assembly filler.
[0021] Further, the preparation method of the modified cyclosilane comprises the following steps:
[0022] A1. Add 2,4,6,8-tetramethylcyclotetrasiloxane, 1-allyloxy-2,3-propylene oxide, chloroplatinic acid and tetrahydrofuran into a reaction kettle, raise the temperature of the reaction kettle to 30-40° C., keep the temperature for 1-2 hours, and perform post-treatment to obtain epoxycyclosilane;
[0023] The reaction equation for preparing epoxy cyclosilane is:
[0024]
[0025] Where: “*” indicates the active linking site of the organic chain segment.
[0026] The reaction principle for preparing epoxy cyclosilane is as follows: under the promotion of a catalyst and heating conditions, the silicon-hydrogen bond on 2,4,6,8-tetramethylcyclotetrasiloxane and the carbon-carbon double bond on 1-allyloxy-2,3-propylene oxide undergo silicon hydrogen addition, and an epoxy group is introduced into the ring structure of 2,4,6,8-tetramethylcyclotetrasiloxane to finally prepare epoxy cyclosilane. The mass spectrometry analysis data of epoxy cyclosilane are m / z: 810.27 (100.0%), 811.27 (48.0%), 812.27 (17.7%), 812.28 (5.5%), 813.27 (4.9%), 813.28 (2.0%), and 814.27 (1.1%).
[0027] A2. Add epoxy cyclosilane, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-benzotriazole, triethylamine and N,N-dimethylformamide into a reaction kettle and stir. Increase the temperature of the reaction kettle to 40-50°C, keep stirring for 1-2 hours, and perform post-treatment to obtain modified cyclosilane.
[0028] The reaction equation for preparing modified cyclosilane is:
[0029]
[0030] Where: “*” indicates the active linking site of the organic chain segment.
[0031] The reaction principle for preparing the modified cyclosilane is as follows: under the catalysis of triethylamine and heating conditions, the epoxy group on the epoxy cyclosilane undergoes a ring-opening reaction to generate free radicals that react with the hydroxyl group on 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-benzotriazole, and finally an anti-ultraviolet group is introduced on the epoxy cyclosilane to obtain the modified cyclosilane. The mass spectrometry data of the modified cyclosilane are m / z: 1737.82 (100.0%), 1738.83 (95.9%), 1739.83(48.3%), 1739.82(28.8%), 1740.83(24.9%), 1738.82(18.5%), 1740.82(12.2%), 1741.83(9.4%), 1741.84(3.3%), 1742.83(2.7%), 1741.82(2.0%), 1742.84(1.5%).
[0032] Furthermore, in step A1, the amount ratio of 2,4,6,8-tetramethylcyclotetrasiloxane, 1-allyloxy-2,3-propylene oxide, chloroplatinic acid and tetrahydrofuran is 8-10g:2-3g:0.2-0.5g:40-60mL, the stirring rate of the reactor is 60-80rpm, and the post-treatment includes: after the reaction is completed, the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is carried out until no liquid is produced to obtain epoxy cyclosilane.
[0033] Furthermore, in step A2, the amount ratio of epoxy cyclosilane, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-benzotriazole, triethylamine and N,N-dimethylformamide is 10-12g:2-3g:0.3-0.5g:45-60mL, the stirring rate of the reactor is 40-60rpm, and the post-treatment includes: after the reaction is completed, the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is extracted to obtain modified cyclosilane.
[0034] Furthermore, the preparation method of the self-assembly substrate comprises the following steps:
[0035] B1. Add tetraethyl orthosilicate, zinc nitrate and deionized water into a reaction kettle, stir at room temperature for 5-10 minutes, adjust the pH of the reaction system to 8-10 with a saturated sodium hydroxide solution, let it stand for 8-12 hours to obtain an aged gel, and then post-treat to obtain a composite particle precursor;
[0036] The reaction principle for preparing the composite particle precursor is as follows: under alkaline conditions, ethyl orthosilicate and zinc nitrate are hydrolyzed to produce a cross-linked structure, an aged gel is obtained after static aging, and a composite particle precursor with a stable structure is obtained after drying.
[0037] B2, transferring the composite particle precursor to a tube furnace for heat treatment to obtain composite particles;
[0038] The reaction principle for preparing composite particles is as follows: during the calcination process, the organic components are burned off, and the remaining inorganic network condenses due to the high temperature and is transformed into more stable oxide nanoparticles. After water vapor is introduced, when the water vapor contacts the high-temperature surface of the nanoparticles, the water molecules are decomposed into hydroxyl groups and hydrogen atoms through the dissociation and surface adsorption of the water molecules. The hydroxyl groups are bound to the surface of the nanoparticles through chemical adsorption to form stable surface hydroxylation.
[0039] B3. Add the composite particles, dioctyltin dichloride and N,N-dimethylformamide into the reactor, introduce nitrogen protection, and then drop 3-isocyanatepropyltrimethoxysilane solution into the reactor. Raise the temperature of the reactor to 35-45°C, keep the reaction warm for 30-40 minutes, and perform post-treatment to obtain a self-assembled substrate.
[0040] The reaction equation for preparing the self-assembled substrate is:
[0041]
[0042] The reaction principle for preparing the self-assembly substrate is as follows: under the catalysis of a catalyst and heating conditions, the hydroxyl groups on the surface of the composite particles react with the isocyanate groups on 3-isocyanatepropyltrimethoxysilane to finally prepare the self-assembly substrate.
[0043] Furthermore, in step B1, the dosage ratio of tetraethyl orthosilicate, zinc nitrate and deionized water is 2-3g:4-6g:80-100mL, and the post-treatment includes: transferring the aged gel to a drying oven at a temperature of 60°C and vacuum drying the material until the material has a constant weight, grinding it with a mill and then passing it through a 400-600 mesh sieve to obtain a composite particle precursor.
[0044] Furthermore, in step B2, the heat treatment is as follows: the composite particle precursor is transferred to a tubular furnace, nitrogen is introduced for protection, the tubular furnace is heated to 500-600°C at a heating rate of 3-5°C / min, and after keeping warm for 2-4 hours, the reactor is naturally cooled to 100-150°C, the nitrogen is disconnected, water vapor is introduced at a flow rate of 1-2L / min, and the heat treatment is carried out for 1-2 hours to obtain composite particles.
[0045] Furthermore, in step B3, the amount ratio of the composite particles, dioctyltin dichloride, N,N-dimethylformamide and 3-isocyanatepropyltrimethoxysilane solution is 8-10g:1-2g:30-40mL:10-15mL, and the 3-isocyanatepropyltrimethoxysilane solution is obtained by mixing 3-isocyanatepropyltrimethoxysilane and N,N-dimethylformamide in an amount ratio of 1g:3-5mL. The post-treatment includes: filtering the reaction liquid to collect the filter cake, washing the filter cake with anhydrous ethanol for 3-5 times, and transferring the filter cake to a drying oven at a temperature of 60°C for vacuum drying until the filter cake has a constant weight to obtain a self-assembled substrate.
[0046] The present invention has the following beneficial effects:
[0047] 1. The present invention modifies hydroxyl groups on the surface of composite particles having silicon and titanium as two components, then modifies siloxane segments, and modifies anti-ultraviolet groups on cyclic silicon-based monomers, and uses the two to polymerize and end-cap to obtain a self-assembled filler with surface cross-linked double bonds, thereby overcoming the defect that inorganic particles have poor dispersibility in organic bodies, and the internal silicon component and siloxane segments coordinate to enhance its corrosion resistance, and the anti-ultraviolet groups on the surface of the composite filler and the internal titanium dioxide component coordinate to ultimately significantly enhance the anti-ultraviolet performance of the material, and finally uses ethylene gas as a matrix to self-assemble and enrich its organic segments, and then polymerizes with vinyl acetate solution to obtain modified EVA, which is melt-blended and extruded with auxiliary materials to obtain corrosion-resistant and UV-resistant photovoltaic packaging materials.
[0048] 2. The composite particle precursor prepared by the present invention has a large number of hydroxyl groups on the surface after being modified with high-temperature steam to obtain composite particles, and the composite particles are further modified with 3-isocyanatepropyltrimethoxysilane to have a large number of siloxane groups on the surface to obtain a self-assembling substrate; in the process of preparing the self-assembling filler, the silicon component of the self-assembling substrate enhances its affinity with the siloxane chain segment, promotes the hydrolysis of a large number of siloxanes and modified cyclosilanes on its surface to form a cross-linked structure, and finally introduces a large number of siloxane segments on its surface through 1,3-divinyl-1,3-dimethyl-1,3-diphenyldisiloxane end-capping, and finally, as a self-assembling filler, ethylene is freely polymerized on its surface to form a complex spatial network structure, thereby significantly improving the mechanical strength and cross-linking degree of the material.
[0049] 3. After surface modification, a large number of hydroxyl groups are introduced into the surface of the composite particles prepared by the present invention, which is conducive to the uniform and efficient introduction of 3-isocyanatepropyltrimethoxysilane into the surface of the composite particles, so that the self-assembled substrate is dispersed more evenly during the hydrolysis of a large number of siloxanes and modified cyclosilanes on the surface to form a cross-linked structure, and the silicon component and siloxane segment inside it coordinate with each other to enhance its corrosion resistance; in the process of preparing the modified EVA, the organic component on the surface of the self-assembled filler makes the self-assembled filler uniformly dispersed inside the photovoltaic packaging material, and the anti-ultraviolet groups on the surface of the composite filler and the titanium dioxide component inside cooperate with each other to ultimately significantly enhance the anti-ultraviolet performance of the material. DETAILED DESCRIPTION
[0050] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] Example 1
[0052] This embodiment provides a self-assembly substrate for preparing a corrosion-resistant photovoltaic encapsulation material, comprising the following steps:
[0053] Step ①: Preparation of composite particle precursor
[0054] Weigh: 200.0g of tetraethyl orthosilicate, 400.0g of zinc nitrate and 8.0L of deionized water and add them into a reactor. After stirring at room temperature for 5 minutes, use saturated sodium hydroxide solution to adjust the pH of the reaction system to 8, and let it stand for 8 hours to obtain an aged gel. Transfer the aged gel to a drying oven at a temperature of 60°C and vacuum dry it until the material has constant weight. Then use a mill to grind it and pass it through a 600-mesh sieve to obtain a composite particle precursor.
[0055] Step ②: Preparation of composite particles
[0056] 600.0 g of the composite particle precursor was transferred to a tubular furnace and nitrogen was introduced for protection. The temperature of the tubular furnace was increased to 500°C at a heating rate of 3°C / min. After being kept warm for 2 hours, the reactor was naturally cooled to 100°C, the nitrogen was disconnected, and water vapor was introduced at a flow rate of 1 L / min. The mixture was kept warm for 1 hour to obtain composite particles.
[0057] Step ③: Preparation of self-assembly substrate
[0058] Weigh: 100.0 g of 3-isocyanate propyl trimethoxy silane and 300.0 mL of N,N-dimethylformamide and mix to obtain a 3-isocyanate propyl trimethoxy silane solution;
[0059] Weigh: 800.0g of composite particles, 100.0g of dioctyltin dichloride and 3.0LN,N-dimethylformamide are added to a reactor. After nitrogen protection is introduced, 1.0L of 3-isocyanatepropyltrimethoxysilane solution is added dropwise to the reactor. The temperature of the reactor is raised to 35°C and the reaction is kept warm for 30 minutes. The reaction liquid is filtered to collect the filter cake. After washing the filter cake with anhydrous ethanol for 3 times, the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight to obtain a self-assembled substrate.
[0060] Example 2
[0061] This embodiment provides a self-assembly substrate for preparing a corrosion-resistant photovoltaic encapsulation material, comprising the following steps:
[0062] Step ①: Preparation of composite particle precursor
[0063] Weigh: 300.0g of tetraethyl orthosilicate, 600.0g of zinc nitrate and 10.0L of deionized water, add into the reactor, stir at room temperature for 10min, adjust the pH value of the reaction system to 10 with saturated sodium hydroxide solution, let it stand for 12h to obtain aged gel, transfer the aged gel to a drying oven at 60°C and vacuum dry until the material has constant weight, grind it with a grinder and pass it through a 400-mesh sieve to obtain a composite particle precursor.
[0064] Step ②: Preparation of composite particles
[0065] The 600.0 composite particle precursor was transferred to a tubular furnace and nitrogen was introduced for protection. The temperature of the tubular furnace was increased to 600°C at a heating rate of 5°C / min. After keeping the temperature for 4 hours, the reactor was naturally cooled to 150°C, the nitrogen was disconnected, and water vapor was introduced at a flow rate of 2L / min. The temperature was kept for 2 hours to obtain composite particles.
[0066] Step ③: Preparation of self-assembly substrate
[0067] Weigh: 100.0 g of 3-isocyanate propyl trimethoxy silane and 500.0 mL of N,N-dimethylformamide and mix to obtain a 3-isocyanate propyl trimethoxy silane solution;
[0068] Weigh: 1000.0g of composite particles, 200.0g of dioctyltin dichloride and 4.0LN,N-dimethylformamide are added to a reactor. After nitrogen protection is introduced, 1.5L of 3-isocyanatepropyltrimethoxysilane solution is added dropwise to the reactor. The temperature of the reactor is raised to 45°C and the reaction is kept warm for 40 minutes. The reaction liquid is filtered to collect the filter cake. After washing the filter cake with anhydrous ethanol for 5 times, the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight to obtain a self-assembled substrate.
[0069] Example 3
[0070] This embodiment provides a self-assembly substrate for preparing a corrosion-resistant photovoltaic encapsulation material, comprising the following steps:
[0071] Step ①: Preparation of composite particle precursor
[0072] Weigh: 250.0g of tetraethyl orthosilicate, 500.0g of zinc nitrate and 9.0L of deionized water and add them into a reactor. After stirring at room temperature for 8 minutes, use saturated sodium hydroxide solution to adjust the pH of the reaction system to 9, and let it stand for 10 hours to obtain an aged gel. Transfer the aged gel to a drying oven at a temperature of 60°C and vacuum dry it until the material has constant weight. Then use a mill to grind it and pass it through a 500-mesh sieve to obtain a composite particle precursor.
[0073] Step ②: Preparation of composite particles
[0074] 600.0 g of the composite particle precursor was transferred to a tubular furnace and nitrogen was introduced for protection. The temperature of the tubular furnace was increased to 540°C at a heating rate of 4°C / min. After being kept warm for 3 hours, the reactor was naturally cooled to 125°C, the nitrogen was disconnected, and water vapor was introduced at a flow rate of 1.5 L / min. The mixture was kept warm for 1-2 hours to obtain composite particles.
[0075] Step ③: Preparation of self-assembly substrate
[0076] Weigh: 100.0 g of 3-isocyanate propyl trimethoxy silane and 400.0 mL of N,N-dimethylformamide and mix to obtain a 3-isocyanate propyl trimethoxy silane solution;
[0077] Weigh: 900.0g of composite particles, 150.0g of dioctyltin dichloride and 3.5LN,N-dimethylformamide are added to a reactor. After nitrogen protection is introduced, 1.2L of 3-isocyanatepropyltrimethoxysilane solution is added dropwise to the reactor. The temperature of the reactor is raised to 40°C and the reaction is kept warm for 35 minutes. The reaction liquid is filtered to collect the filter cake. After washing the filter cake with anhydrous ethanol for 4 times, the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight to obtain a self-assembled substrate.
[0078] Example 4
[0079] This embodiment provides a method for preparing a corrosion-resistant photovoltaic encapsulation material, comprising the following steps:
[0080] Step 1: Preparation of modified cyclosilane
[0081] Weigh: 800.0g 2,4,6,8-tetramethylcyclotetrasiloxane, 200.0g 1-allyloxy-2,3-propylene oxide, 20.0g chloroplatinic acid and 4.0L tetrahydrofuran are added into a reactor, the temperature of the reactor is raised to 30°C, and the reaction is kept warm for 1h. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added into a rotary evaporator with a water bath temperature of 80°C, and distilled under reduced pressure until no liquid is produced to obtain epoxy cyclosilane;
[0082] Weigh: 1000.0g epoxy cyclosilane, 200.0g 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-benzotriazole, 30.0g triethylamine and 4.5L N,N-dimethylformamide, add into the reactor and stir at a stirring rate of 40rpm. The temperature of the reactor is raised to 40°C and stirred for 1h. After the reaction is completed, the reactor is cooled to room temperature and the reaction liquid is added into a rotary evaporator with a water bath temperature of 80°C. It is distilled under reduced pressure until no liquid is produced to obtain modified cyclosilane.
[0083] Step 2: Preparation of self-assembling fillers
[0084] Weigh: 500.0g of modified cyclosilane, 800.0g of the self-assembly substrate prepared in Example 1 and 4.0L of ether are added to a reactor, stirred at room temperature for 12min, 100.0mL of 98.0wt% sulfuric acid solution is added dropwise to the reactor, and the reaction is kept warm for 4h at room temperature. 200.0g of 1,3-divinyl-1,3-dimethyl-1,3-diphenyldisiloxane is continued to be added to the reactor. After reacting for 2h, solid sodium bicarbonate is added to the reactor until the pH of the reaction solution is 7, the reaction solution is filtered to collect the filter cake, the filter cake is washed 3 times with anhydrous ethanol and deionized water, and then the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight to obtain a self-assembling filler.
[0085] Step 3: Preparation of modified EVA
[0086] Weigh: 1000.0g of self-assembled filler and 200.0g of azobisisobutyronitrile are placed in a high-pressure reactor, the temperature of the high-pressure reactor is increased to 120-150°C, the pressure is increased to 12MPa, 8.0kg of ethylene is introduced, and the polymerization is carried out at constant temperature and pressure for 40min to obtain a modified EVA precursor;
[0087] Weigh: 700.0g of modified EVA precursor, 200.0g of vinyl acetate and 3.0L of o-xylene are added to the reactor, the temperature of the reactor is raised to 120°C, and after stirring for 10 minutes, 50.0g of azobisisobutyronitrile is added to the reactor, and the reaction is kept warm for 1 hour. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 80°C, and distilled under reduced pressure until no liquid is produced to obtain modified EVA.
[0088] Step 4: Preparation of photovoltaic packaging materials
[0089] Weigh: 8.5 kg of modified EVA, 50.0 g of 2-hydroxy-4-octyloxyphenol, 50.0 g of 2,6-di-tert-butyl-p-cresol, 400.0 g of dioctyl phthalate and 500.0 g of tert-butyl peroxide (2-ethylhexanoate) and add them into a twin-screw extruder. The temperatures of the 8 temperature zones of the twin-screw extruder from the feed end to the discharge end are 180°C, 185°C, 195°C, 195°C, 210°C, 215°C, 215°C, 220°C, the spindle speed is 60 rpm, the pressure is 100 bar, and the photovoltaic encapsulation material is obtained by melt extrusion.
[0090] Example 5
[0091] This embodiment provides a method for preparing a corrosion-resistant photovoltaic encapsulation material, comprising the following steps:
[0092] Step 1: Preparation of modified cyclosilane
[0093] Weigh: 1000.0g 2,4,6,8-tetramethylcyclotetrasiloxane, 300.0g 1-allyloxy-2,3-propylene oxide, 50.0g chloroplatinic acid and 6.0L tetrahydrofuran are added into a reactor, the temperature of the reactor is raised to 40°C, and the reaction is kept warm for 2h. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added into a rotary evaporator with a water bath temperature of 100°C, and distilled under reduced pressure until no liquid is produced to obtain epoxy cyclosilane;
[0094] Weigh: 1200.0g epoxy cyclosilane, 300.0g 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-benzotriazole, 50.0g triethylamine and 6.0L N,N-dimethylformamide, add into the reactor and stir at a stirring rate of 60rpm, raise the temperature of the reactor to 50°C, keep stirring for 2h, after the reaction is completed, wait for the reactor to cool to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 100°C, and distill under reduced pressure until no liquid is produced to obtain modified cyclosilane.
[0095] Step 2: Preparation of self-assembling fillers
[0096] Weigh: 600.0g of modified cyclosilane, 1000.0g of the self-assembly substrate prepared in Example 2 and 6.0L of ether are added to a reactor. After stirring at room temperature for 16 minutes, 200.0mL of 98.0wt% sulfuric acid solution is added dropwise to the reactor. The reaction is kept warm for 5 hours at room temperature. 300.0g of 1,3-divinyl-1,3-dimethyl-1,3-diphenyldisiloxane is continued to be added to the reactor. After reacting for 4 hours, solid sodium bicarbonate is added to the reactor until the pH of the reaction solution is 8. The reaction solution is filtered to collect the filter cake. After washing the filter cake 5 times with anhydrous ethanol and deionized water, the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight to obtain a self-assembling filler.
[0097] Step 3: Preparation of modified EVA
[0098] Weigh: 2000.0g of self-assembled filler and 300.0g of azobisisobutyronitrile are placed in a high-pressure reactor, the temperature of the high-pressure reactor is increased to 150°C, the pressure is increased to 16MPa, 9.0kg of ethylene is introduced, and the polymerization is carried out at constant temperature and pressure for 60min to obtain a modified EVA precursor;
[0099] Weigh: 800.0g of modified EVA precursor, 300.0g of vinyl acetate and 4.0L of o-xylene are added to the reactor, the temperature of the reactor is raised to 130°C, and after stirring for 15 minutes, 80.0g of azobisisobutyronitrile is added to the reactor, and the reaction is kept warm for 2 hours. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 100°C, and distilled under reduced pressure until no liquid is produced to obtain modified EVA.
[0100] Step 4: Preparation of photovoltaic packaging materials
[0101] Weigh: 9.0 kg of modified EVA, 200.0 g of 2-hydroxy-4-octyloxyphenol, 100.0 g of 2,6-di-tert-butyl-p-cresol, 500.0 g of dioctyl phthalate and 700.0 g of tert-butyl peroxide bis(2-ethylhexanoate) ester, and add them into a twin-screw extruder. The temperatures of the 8 temperature zones of the twin-screw extruder from the feed end to the discharge end are 180°C, 185°C, 195°C, 195°C, 210°C, 215°C, 215°C, and 220°C, respectively. The spindle speed is 80 rpm, the pressure is 150 bar, and the photovoltaic encapsulation material is obtained by melt extrusion.
[0102] Example 6
[0103] This embodiment provides a method for preparing a corrosion-resistant photovoltaic encapsulation material, comprising the following steps:
[0104] Step 1: Preparation of modified cyclosilane
[0105] Weigh: 900.0g 2,4,6,8-tetramethylcyclotetrasiloxane, 250.0g 1-allyloxy-2,3-propylene oxide, 35.0g chloroplatinic acid and 5.0L tetrahydrofuran, add them into a reactor, raise the temperature of the reactor to 35°C, and keep the temperature for 2h. After the reaction is completed, cool the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 90°C, and distill under reduced pressure until no liquid is produced to obtain epoxy cyclosilane;
[0106] Weigh: 1.1 kg of epoxy cyclosilane, 250.0 g of 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-benzotriazole, 40.0 g of triethylamine and 5.0 L of N,N-dimethylformamide, add them into a reactor and stir at a stirring rate of 50 rpm. The temperature of the reactor is raised to 50°C and stirred for 2 hours. After the reaction is completed, the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 90°C, and distilled under reduced pressure until no liquid is produced to obtain modified cyclosilane.
[0107] Step 2: Preparation of self-assembling fillers
[0108] Weigh: 550.0g of modified cyclosilane, 900.0g of the self-assembly substrate prepared in Example 3 and 5.0L of ether are added to a reactor. After stirring at room temperature for 16 minutes, 150.0mL of 98.0wt% sulfuric acid solution is added dropwise to the reactor. The reaction is kept warm for 5 hours at room temperature. 250.0g of 1,3-divinyl-1,3-dimethyl-1,3-diphenyldisiloxane is continued to be added to the reactor. After reacting for 3 hours, solid sodium bicarbonate is added to the reactor until the pH of the reaction solution is 8. The reaction solution is filtered to collect the filter cake. After washing the filter cake 4 times with anhydrous ethanol and deionized water, the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight to obtain a self-assembling filler.
[0109] Step 3: Preparation of modified EVA
[0110] Weigh: 1500.0g of self-assembled filler and 250.0g of azobisisobutyronitrile are placed in a high-pressure reactor, the temperature of the high-pressure reactor is increased to 135°C, the pressure is increased to 14MPa, 8.5kg of ethylene is introduced, and the polymerization is carried out at constant temperature and pressure for 50min to obtain a modified EVA precursor;
[0111] Weigh: 750.0g of modified EVA precursor, 250.0g of vinyl acetate and 3.5L of o-xylene are added to the reactor, the temperature of the reactor is raised to 125°C, and after stirring for 12 minutes, 65.0g of azobisisobutyronitrile is added to the reactor, and the reaction is kept warm for 2 hours. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 90°C, and distilled under reduced pressure until no liquid is produced to obtain modified EVA.
[0112] Step 4: Preparation of photovoltaic packaging materials
[0113] Weigh: 8.8 kg of modified EVA, 100.0 g of 2-hydroxy-4-octyloxyphenol, 75.0 g of 2,6-di-tert-butyl-p-cresol, 450.0 g of dioctyl phthalate and 600.0 g of tert-butyl peroxide bis(2-ethylhexanoate) ester, and add them into a twin-screw extruder. The temperatures of the 8 temperature zones of the twin-screw extruder from the feed end to the discharge end are 180°C, 185°C, 195°C, 195°C, 210°C, 215°C, 215°C, and 220°C, respectively. The spindle speed is 70 rpm, the pressure is 125 bar, and the photovoltaic encapsulation material is obtained by melt extrusion.
[0114] Comparative Example 1
[0115] The difference between this comparative example and Example 6 is that, during the preparation of the self-assembly substrate used, the introduction of water vapor in step ② is omitted.
[0116] Comparative Example 2
[0117] The difference between this comparative example and Example 6 is that step ③ is omitted during the preparation of the self-assembly substrate used.
[0118] Comparative Example 3
[0119] The difference between this comparative example and Example 6 is that step 1 is eliminated, and in step 2, 4, 6, 8-tetramethylcyclotetrasiloxane is used in an equal amount to replace the modified cyclosilane.
[0120] Comparative Example 4
[0121] The difference between this comparative example and Example 6 is that the use of the self-assembly substrate is omitted in step 2.
[0122] Performance Test:
[0123] The tensile strength, elongation at break, crosslinking degree and UV resistance (120 kWh / m 2 ), the specific data are shown in Table 1;
[0124] The percentage changes of various properties of the photovoltaic encapsulation materials prepared in Example 6 and Comparative Examples 1-3 after being immersed in acid solution were measured with reference to the standard GB / T 11547-2008 "Determination of resistance of plastics to liquid chemical reagents". Specific data are shown in Table 2.
[0125] Table 1-Performance test data of each sample
[0126]
[0127]
[0128] Table 2 - Percentage change in performance of each sample
[0129]
[0130] Data Analysis:
[0131] Comparing and analyzing the data in Table 1 above, the photovoltaic encapsulation material prepared by the present invention has a tensile strength of 19 MPa, an elongation at break of 501%, a crosslinking degree of 79%, and a peel strength of 36 N·cm -1 And the yellowing index is 2.0;
[0132] Comparing and analyzing the data in Table 2 above, the change rate of tensile strength, elongation at break, crosslinking degree, peel strength, and yellowing index of the photovoltaic encapsulation material prepared by the present invention after acid immersion is 97.3%, 98.2%, 99.3%, 97.2%, and 72.5% respectively.
[0133] By comparing the data of Example 6 and Comparative Examples 1-2 in Table 1, it can be found that the mechanical strength and cross-linking degree of the photovoltaic encapsulation material prepared in Example 6 are significantly improved. By comparing the data of Example 6 and Comparative Examples 3-4 in Table 1, it can be found that the anti-ultraviolet performance of the photovoltaic encapsulation material prepared in Example 6 is significantly improved.
[0134] It is shown that the mechanical strength and cross-linking degree of the photovoltaic encapsulation material prepared in Example 6 are significantly improved, indicating that the composite particle precursor prepared by the present invention has a large number of hydroxyl groups on the surface after being modified by high-temperature water vapor to obtain composite particles, and the composite particles are further modified by 3-isocyanate propyltrimethoxysilane to have a large number of siloxane groups on the surface to obtain a self-assembled substrate;
[0135] In the process of preparing the self-assembling filler, the silicon component of the self-assembling substrate enhances its affinity with the siloxane chain segment, promotes the hydrolysis of a large amount of siloxane and modified cyclosilane on its surface to form a cross-linked structure, and finally introduces a large amount of siloxane chain segments on its surface through 1,3-divinyl-1,3-dimethyl-1,3-diphenyldisiloxane end-capping. Finally, as a self-assembling filler, ethylene is freely polymerized on its surface to form a complex spatial network structure, thereby significantly improving the mechanical strength and cross-linking degree of the material;
[0136] In the process of preparing modified EVA, the organic components on the surface of the self-assembled filler make the self-assembled filler evenly dispersed inside the photovoltaic encapsulation material, and the anti-ultraviolet groups on the surface of the composite filler and the titanium dioxide components inside cooperated to significantly enhance the anti-ultraviolet performance of the material.
[0137] By comparing the data of Example 6 and Comparative Example 2 and Comparative Example 4 in Table 2, it can be found that the corrosion resistance of the photovoltaic encapsulation material prepared in Example 6 is significantly improved; this indicates that in the process of preparing the substrate in Example 6, the composite particle precursor has a large number of hydroxyl groups on the surface after being modified by high-temperature water vapor to obtain composite particles, and the composite particles are further modified by 3-isocyanate propyltrimethoxysilane to have a large number of siloxane groups on the surface to obtain a self-assembled substrate, and after the surface modification, a large number of hydroxyl groups are introduced into the surface, which is conducive to the uniform and efficient introduction of 3-isocyanate propyltrimethoxysilane into the surface of the composite particles, so that in the process of hydrolyzing a large number of siloxanes and modified cyclosilanes on the surface to form a cross-linked structure, the self-assembled substrate is dispersed more evenly, and the silicon component and siloxane segment inside it coordinate with each other to enhance its corrosion resistance;
[0138] It is explained that the present invention is to modify the hydroxyl group on the surface of the composite particles having the silicon-titanium dual components and then modify the siloxane segment, and modify the anti-ultraviolet group on the cyclic silicon-based monomer, and utilize the two to polymerize and end-cap to obtain a self-assembled filler with surface cross-linked double bonds, thereby overcoming the defect of poor dispersion ability of inorganic particles in organic bodies, using ethylene gas as a matrix to self-assemble and enrich its organic segment, and then polymerizing it with vinyl acetate solution to obtain modified EVA, which is melt-blended and extruded with auxiliary materials to obtain corrosion-resistant and UV-resistant photovoltaic packaging materials.
[0139] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a corrosion-resistant photovoltaic encapsulation material, characterized in that: The following steps are involved: S1. Place the self-assembly filler and azobisisobutyronitrile in a high-pressure reactor, increase the temperature of the high-pressure reactor to 120-150° C., increase the pressure to 12-16 MPa, introduce ethylene, and polymerize at constant temperature and pressure for 40-60 minutes to obtain a modified EVA precursor; S2, adding the modified EVA precursor, vinyl acetate and o-xylene into a reactor, raising the temperature of the reactor to 120-130°C, stirring for 10-15 minutes, adding azobisisobutyronitrile into the reactor, keeping the temperature for 1-2 hours, and post-treating to obtain the modified EVA; S3, adding the modified EVA and auxiliary materials into a twin-screw extruder, and melt-extrude to obtain photovoltaic encapsulation materials.
2. The method for preparing a corrosion-resistant photovoltaic encapsulation material according to claim 1, characterized in that: In step S1, the amount ratio of self-assembly filler, azobisisobutyronitrile and ethylene is 10-20g:2-3g:80-90g; in step S2, the amount ratio of modified EVA precursor, vinyl acetate, o-xylene and azobisisobutyronitrile is 7-8g:2-3g:30-40mL:0.5-0.8g.
3. The method for preparing a corrosion-resistant photovoltaic encapsulation material according to claim 1, characterized in that: In step S3, the usage ratio of modified EVA and auxiliary materials is 85-90g:10-15g, the auxiliary materials include ultraviolet absorber, antioxidant, plasticizer and crosslinking agent, and the usage ratio of ultraviolet absorber, antioxidant, plasticizer and crosslinking agent is 0.5-2g:0.5-1g:4-5g:5-7g.
4. The method for preparing a corrosion-resistant photovoltaic encapsulation material according to claim 1, characterized in that: The preparation method of the self-assembling filler comprises the following steps: adding modified cyclosilane, a self-assembling substrate and ether into a reaction kettle, stirring at room temperature for 12-16 minutes, dripping 98.0wt% sulfuric acid solution into the reaction kettle, keeping the temperature at room temperature for reaction for 4-5 hours, continuously adding a terminator into the reaction kettle, reacting for 2-4 hours, adding solid sodium bicarbonate into the reaction kettle until the pH value of the reaction solution is 7-8, and post-treating to obtain the self-assembling filler.
5. The method for preparing a corrosion-resistant photovoltaic encapsulation material according to claim 3, characterized in that: The dosage ratio of modified cyclosilane, self-assembly substrate, ether, 98wt% sulfuric acid solution and terminator is 5-6g:8-10g:40-60mL:1-2mL:2-3g, and the terminator is 1,3-divinyl-1,3-dimethyl-1,3-diphenyldisiloxane.
6. The method for preparing a corrosion-resistant photovoltaic encapsulation material according to claim 3, characterized in that: The preparation method of the modified cyclosilane comprises the following steps: A1. Add 2,4,6,8-tetramethylcyclotetrasiloxane, 1-allyloxy-2,3-propylene oxide, chloroplatinic acid and tetrahydrofuran into a reaction kettle, raise the temperature of the reaction kettle to 30-40° C., keep the temperature for 1-2 hours, and perform post-treatment to obtain epoxycyclosilane; A2. Add epoxy cyclosilane, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-benzotriazole, triethylamine and N,N-dimethylformamide into a reaction kettle and stir. Increase the temperature of the reaction kettle to 40-50°C, keep stirring for 1-2 hours, and perform post-treatment to obtain modified cyclosilane.
7. The method for preparing a corrosion-resistant photovoltaic encapsulation material according to claim 3, characterized in that: In step A1, the amount ratio of 2,4,6,8-tetramethylcyclotetrasiloxane, 1-allyloxy-2,3-propylene oxide, chloroplatinic acid and tetrahydrofuran is 8-10g:2-3g:0.2-0.5g:40-60mL, and the stirring rate of the reactor is 60-80rpm; in step A2, the amount ratio of epoxycyclosilane, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-benzotriazole, triethylamine and N,N-dimethylformamide is 10-12g:2-3g:0.3-0.5g:45-60mL, and the stirring rate of the reactor is 40-60rpm.
8. The method for preparing a corrosion-resistant photovoltaic encapsulation material according to claim 3, characterized in that: The preparation method of the self-assembly substrate comprises the following steps: B1. Add tetraethyl orthosilicate, zinc nitrate and deionized water into a reactor, stir at room temperature for 5-10 minutes, adjust the pH of the reaction system to 8-10 with a saturated sodium hydroxide solution, let it stand for 8-12 hours to obtain an aged gel, and then post-treat to obtain a composite particle precursor; B2, transferring the composite particle precursor to a tube furnace for heat treatment to obtain composite particles; B3. Add the composite particles, dioctyltin dichloride and N,N-dimethylformamide into the reactor, introduce nitrogen protection, and then drop 3-isocyanatepropyltrimethoxysilane solution into the reactor. Raise the temperature of the reactor to 35-45°C, keep the reaction warm for 30-40 minutes, and perform post-treatment to obtain a self-assembled substrate.
9. The method for preparing a corrosion-resistant photovoltaic encapsulation material according to claim 8, characterized in that: In step B1, the dosage ratio of ethyl orthosilicate, zinc nitrate and deionized water is 2-3g:4-6g:80-100mL; in step B3, the dosage ratio of composite particles, dioctyltin dichloride, N,N-dimethylformamide and 3-isocyanatepropyltrimethoxysilane solution is 8-10g:1-2g:30-40mL:10-15mL, and the 3-isocyanatepropyltrimethoxysilane solution is obtained by mixing 3-isocyanatepropyltrimethoxysilane and N,N-dimethylformamide at a dosage ratio of 1g:3-5mL.
10. The method for preparing a corrosion-resistant photovoltaic encapsulation material according to claim 8, characterized in that: In step B2, the heat treatment is as follows: the composite particle precursor is transferred to a tubular furnace, nitrogen is introduced for protection, the tubular furnace is heated to 500-600°C at a heating rate of 3-5°C / min, and after keeping warm for 2-4 hours, the reactor is naturally cooled to 100-150°C, the nitrogen is disconnected, and water vapor is introduced at a flow rate of 1-2L / min, and the heat treatment is carried out for 1-2 hours to obtain composite particles.
Citation Information
Patent Citations
A UV-blocking EVA photovoltaic film, its preparation method, and a photovoltaic module thereof.
CN114854331B
EVA hot melt adhesive for storage battery
CN105778827A
Heat-resistant packaging material, preparation method and application in solar cell
CN119101477A